2020
DOI: 10.5501/wjv.v9.i3.38
|View full text |Cite
|
Sign up to set email alerts
|

Chinese medical students’ interest in COVID-19 pandemic

Abstract: BACKGROUND The outbreak of coronavirus disease 2019 (COVID-19) happened in early December and it has affected China in more ways than one. The societal response to the pandemic restricted medical students to their homes. Although students cannot learn about COVID-19 through clinical practice, they can still pay attention to news of COVID-19 through various channels. Although, as suggested by previous studies, some medical students have already volunteered to serve during the COVID-19 pandemic, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 21 publications
4
34
3
2
Order By: Relevance
“…Interestingly, the likelihood decreased with school grade: ORs = 0.44 (95% CIs: 0.27-0.74) in second year, ORs = 0.31 (95% CIs: 0.18-0.52) in third year, and ORs = 0.20 (95% CIs: 0.12-0.33) in fourth-year students. After removing the independent variable "choosing nursing as career before COVID-19 pandemic" which contributed the most to the model (OR = 66.9), fourth year students were still less likely to choose nursing as future career compared to the first grade students (OR = 0.50, 95% CI: 0.35-0.72), which is consistent with the findings in medical students (42). A recent study of Chinese medical students found that senior grade students were less likely to be volunteers combating the COVID-19 pandemic compared to junior and middle grade students (42), probably due to the risk of COVID-19 infection during the pandemic and relatively low income for junior doctors.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Interestingly, the likelihood decreased with school grade: ORs = 0.44 (95% CIs: 0.27-0.74) in second year, ORs = 0.31 (95% CIs: 0.18-0.52) in third year, and ORs = 0.20 (95% CIs: 0.12-0.33) in fourth-year students. After removing the independent variable "choosing nursing as career before COVID-19 pandemic" which contributed the most to the model (OR = 66.9), fourth year students were still less likely to choose nursing as future career compared to the first grade students (OR = 0.50, 95% CI: 0.35-0.72), which is consistent with the findings in medical students (42). A recent study of Chinese medical students found that senior grade students were less likely to be volunteers combating the COVID-19 pandemic compared to junior and middle grade students (42), probably due to the risk of COVID-19 infection during the pandemic and relatively low income for junior doctors.…”
Section: Discussionsupporting
confidence: 83%
“…After removing the independent variable "choosing nursing as career before COVID-19 pandemic" which contributed the most to the model (OR = 66.9), fourth year students were still less likely to choose nursing as future career compared to the first grade students (OR = 0.50, 95% CI: 0.35-0.72), which is consistent with the findings in medical students (42). A recent study of Chinese medical students found that senior grade students were less likely to be volunteers combating the COVID-19 pandemic compared to junior and middle grade students (42), probably due to the risk of COVID-19 infection during the pandemic and relatively low income for junior doctors. Intention to be volunteers and career choice in medical or nursing students may be associated with workplace safety such as provision of personal protective equipment (43,44).…”
Section: Discussionsupporting
confidence: 83%
“…Response and perspectives on the medical student role varied globally at this time [ 5 – 9 ]. Medical students have previously assumed greater responsibility and made valuable contributions during historic times of need, however in some areas medical students were viewed as non-essential in the healthcare environment [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Response and perspectives on the medical student role varied globally at this time (5)(6)(7)(8)(9). Medical students have previously assumed greater responsibility and made valuable contributions during historic times of need, however in some areas medical students were viewed as non-essential in the healthcare environment (10).…”
Section: Introductionmentioning
confidence: 99%